2003
DOI: 10.5465/amr.2003.8925236
|View full text |Cite
|
Sign up to set email alerts
|

The Social Side of Creativity: A Static and Dynamic Social Network Perspective

Abstract: Each copy of any part of a JSTOR transmission must contain the same copyright notice that appears on the screen or printed page of such transmission.JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Academy of Management is col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
668
2
19

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,135 publications
(710 citation statements)
references
References 66 publications
21
668
2
19
Order By: Relevance
“…We addressed the phenomenon that learning and vitality at work are influenced by external variables to generate innovation. We showed that external social relations are positively related to thriving and innovation, suggesting that information emanating from diverse sources is more novel and inspiring (Perry-Smith and Shalley 2003), and intensifies the feeling of thriving. This, in turn, leads to innovation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We addressed the phenomenon that learning and vitality at work are influenced by external variables to generate innovation. We showed that external social relations are positively related to thriving and innovation, suggesting that information emanating from diverse sources is more novel and inspiring (Perry-Smith and Shalley 2003), and intensifies the feeling of thriving. This, in turn, leads to innovation.…”
Section: Discussionmentioning
confidence: 94%
“…Employees are simultaneously embedded in external workgroup connections (Cropanzano and Mitchell 2005;Granovetter 1981;Krackhardt 1992;Perry-Smith and Shalley 2003). Infrequent external work contacts are a source of non-redundant information and facilitate several processes that help innovative work behavior, including opportunities for exploration, sources of ideas, and support to implement innovations (Cole et al 2002;De Jong and Den Hartog 2010;Wang et al 2015).…”
Section: Interaction Effect Of External Work Contactsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the current literature on this matter mentions that in crowdsourcing competitions, effective social relationships improve individual creativity and innovation (Bullinger, Neyer, Rass, & Moeslein, 2010;Kanter, 1988;Perry-Smith & Shalley, 2003).…”
Section: Crowdsourcing Contests: Participant-company Relationshipmentioning
confidence: 99%
“…Taking into account such an unstable environment, the issue that becomes signifi cant is enhancing organizational capacity to respond to external changes with some novel products, processes, ideas etc. (Nonaka & Takeuchi, 1995;Bessant, Lamming, Noke, & Philips, 2005;Bessant & Tidd, 2007;Ellonen, Blomqvist, & Puumalainen, 2008;Pietrzak & Łapińska, 2015).…”
Section: Introductionmentioning
confidence: 99%